Examining the Level of Accountability and Transparency with Respect to Political Party Financing in Timor Leste - Celso da Fonseca; Joel Mark Baysa-Barredo (Asia-Pacific Journal of Elections and Democracy, 2021)
The democratization process in Timor-Leste as a post-conflict country, developing economy and fragile state requires good governance, accountability, and transparency. In this light, political actors, such as parties, are expected to play an essential role in this achievement. However, accountability and transparency of the political parties’ funding and financial execution remain questionable in this tiny, young nation. There are a number of legal safeguards to ensure political party accountability and transparency concerning fund acquisition and use. However, it can be argued that monitoring financial status of political parties has been challenging, as sources have never been fully publicly revealed nor scrutinized. This has serious implications on the level of accountability and transparency amongst political actors, as well as, on the democratic process in Timor-Leste, as a whole. There is, indeed, a need for systemic reform, particularly in the area of publishing and auditing financial activities of political parties. Judicial and investigative functions of relevant State agencies have to be either developed or fortified. On a more philosophical sense, Timor Leste’s political actors are expected more aware about and fully committed to their roles and responsibilities towards the country’s democratization and the attainment of a well-informed and empowered society.